Pedagogical conditions as the main factor of the of future lawyers’ educational competences formation - Boreichuk, Anna (Journal of Education, Health and Sport, 2017)
The author's characteristic of the process of harmonization of pedagogical conditions with a conceptually developed model of formation of educational competences of future lawyers is given in the article. The author's vision for interpreting the concepts "pedagogical conditions", "educational competence", "educational and activity technologies", etc. is presented. Principles of interaction of model components with each type of pedagogical conditions and its efficiency are proved. The main component of the model is argued to be educational and activity technologies and appropriate evidences are showed. Effectiveness of the model is supported by the use of a certain group of methods, which the author distinguishes from the generality. The author demonstrates the effectiveness of the proposed pedagogical conditions and the conceptual model by presenting the results of the research.